Properties of ZnO Nanopowders Synthesized by Glycine-Nitrate Gel Combustion - Yildiz, O.; Soydan, A. M.; Ipcizade, E. F.; Akin, D.; Ucak, O. (Polish Acad Sciences Inst Physics, 2014)
The morphology and other physical properties of ZnO nanopowders synthesized by glycine-nitrate gel combustion process were investigated and characterized by scanning electron microscopy, transmission electron microscopy, nanosizer and X-ray diffraction. Glycine, NH2CH2COOH, and zinc nitrate Zn(NO3)(2)center dot 6H(2)O were dissolved in distilled water and the solution was coagulated by mixing at 90 degrees C. The viscous gel prepared during glycine-nitrate mixing was heated at approximate to 220 degrees C to initiate the exothermic reactions by self-combustion where the temperature reached up to 1200 degrees C. The glycine-nitrate ratio had a significant effect on the reaction temperature and final particle morphology. Therefore the synthesized powders have a different morphology like formless and spherical tufa ash. The particle size distribution was 50-1200 nm as measured using a nanosizer.
3rd International Congress on Advances in Applied Physics and Materials Science -- APR 24-28, 2013 -- Antalya, TURKEY
Keywords: Powder